Pengaruh Prinsip Good Governance dan E-Service terhadap Kepuasan Masyarakat dalam Menggunakan Aplikasi Mobile JKN di Badan Penyelenggara Jaminan Sosial (BPJS) Kesehatan Cabang Kota Ambon - Nadhia Safira Mansur; Hendry Selanno; La Madjid (MAN 4 Kota Pekanbaru, 2026)
This study examines the influence of good governance principles and e-service quality on public satisfaction in using the Mobile JKN application at BPJS Health, Ambon City Branch. The rapid development of digital public services requires government institutions to ensure that technology-based services are supported by effective governance practices. This research aims to analyze how the implementation of good governance and the performance of digital services contribute to users’ perceptions and satisfaction with the Mobile JKN application. A quantitative approach was employed using multiple linear regression analysis to assess the relationship between the independent variables and public satisfaction as the dependent variable. The results indicate that good governance has a significant positive effect on public satisfaction (β = 0.421; t = 5.701; Sig. = 0.000), as does e-service quality (β = 0.510; t = 6.909; Sig. = 0.000). Simultaneously, good governance and e-service quality significantly influence public satisfaction, as evidenced by an F-value of 145.328 with a significance level of 0.000. The coefficient of determination (R²) of 0.861 indicates that 86.1% of the variation in public satisfaction can be explained by the two independent variables, while the remaining 13.9% is influenced by other factors outside the model. These findings highlight that the integration of sound governance practices and high-quality digital services is essential for improving user satisfaction in technology-based public health services. Strengthening governance mechanisms and continuously enhancing digital service performance are therefore crucial strategies for increasing public satisfaction with the Mobile JKN application.